Seaweed for Healthy People: Seaweed-Based Health Products - Erna Susilawati; Heriani; Herwandi Sape; Niken Ayu Andira; Ripki Adiaksa (Jurnal PKM: Karya dan Inovasi untuk Negeri, 2025)
This Community Service Program (PKM) was carried out in Binaga Sangkara Village, Maros Regency, with the aim of increasing community knowledge about the health benefits of seaweed and encouraging its local utilization. The background of this activity is based on the global rise of non-communicable diseases (NCDs) due to poor dietary habits, as well as the underutilization of seaweed among coastal communities as a functional food source. The program included nutrition education, socialization of seaweed benefits, and training in seaweed-based food processing. Evaluation results showed a significant improvement in participants' knowledge, with those in the high-knowledge category increasing from 20% to 60% after the program. Additionally, there was a growing interest among residents in developing seaweed products independently. This activity demonstrates that an educative-participative approach can effectively raise nutritional awareness and empower coastal communities through the sustainable use of local resources.